2019
DOI: 10.1093/nc/niz017
|View full text |Cite
|
Sign up to set email alerts
|

Induced illusory body ownership in borderline personality disorder

Abstract: One aspect of selfhood that may have relevance for borderline personality disorder (BPD) is variation in sense of body ownership. We employed the rubber hand illusion to manipulate sense of body ownership in BPD. We extended previous research on illusory body ownership in BPD by testing: (i) two illusion conditions: asynchronous and synchronous stimulation, (ii) relationship between illusion experience and BPD symptoms, and (iii) relationship between illusion experience and maladaptive personality traits. We m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 57 publications
6
38
0
Order By: Relevance
“…Only two studies have investigated RHI in BPD patients. Both studies report an increased illusory limb ownership in adult women with BPD compared to healthy controls (Bekrater-Bodmann et al, 2016;Neustadter et al, 2019). Interestingly, one of these studies showed that this increased illusion occured not only in the synchronous condition, but also in the asynchronous condition (Neustadter et al, 2019).…”
Section: The Minimal Self In Bpdmentioning
confidence: 96%
See 3 more Smart Citations
“…Only two studies have investigated RHI in BPD patients. Both studies report an increased illusory limb ownership in adult women with BPD compared to healthy controls (Bekrater-Bodmann et al, 2016;Neustadter et al, 2019). Interestingly, one of these studies showed that this increased illusion occured not only in the synchronous condition, but also in the asynchronous condition (Neustadter et al, 2019).…”
Section: The Minimal Self In Bpdmentioning
confidence: 96%
“…With respect to proprioceptive drift, both studies report similar drift toward the rubber hand in the synchronous condition in BPD and healthy controls groups. Nonetheless, BPD participants also showed a sustained proprioceptive drift during the asynchronous condition in one study (Neustadter et al, 2019). In addition, Bekrater-Bodmann and colleagues showed that state and trait dissociations were both associated with illusory limb ownership but not significantly associated with proprioceptive drift (Bekrater-Bodmann et al, 2016).…”
Section: The Minimal Self In Bpdmentioning
confidence: 96%
See 2 more Smart Citations
“…And indeed, people with BPD, who are highly influenced by social cues, have increased susceptibility even to the canonically less illusion-inducing asynchronous condition of the rubber hand illusion task. 43 Therefore, the hypothesis put forth by Lush et al. that direct measurement of hypnotizability may help to control for the contribution of high phenomenological control in participant responses may also have particular relevance for research in people with BPD.…”
Section: How Bpd Research Can Better Engage Bpd-specific Featuresmentioning
confidence: 99%